Manajamen Pengorganisasian Program Kursus Bahasa Arab Leesan Arabic Pekanbaru - Yolanda, Refiyana; Mufidah, Nuril (Diwan Media Pustaka, 2023)
Organizing management is carried out through planning an effective course program with a good program, conducting regular evaluations as well as maintaining a good reputation. The purpose of this study is to describe; 1) formulation of Arabic learning programs 2) management of human resources in carrying out learning programs 3) design of efficient organizational structures. This research is a descriptive qualitative research type of case study. The data collection used is learning observation and evaluation meetings. Interviews with managers, quality guarantors, administrative staff, financial staff and teaching staff. Documentation in the form of an organizational structure. The subject of this study is an employee of Leesan Arabic Pekanbaru, Indonesia in 2023. The techniques used in collecting this research data involved participant observation, in-depth interviews, and documentation. Observations about the process of continuity of the Arabic course program. The interview was conducted to find out the organization of the course institution in running the Arabic language program by involving the management of the institution, quality guarantor, administrative staff, financial staff and teaching staff of one person. In this study, the data analysis technique follows the approach adopted from the Miles and Huberman model, which consists of three stages, namely data reduction, data presentation, and conclusions. The results of this study found: 1) the formulation of Arabic language course programs based on student needs, there are 5 programs, namely regular Arabic, Middle East study preparation, dauroh qawa'id I, dauroh qawa'id II, and dauroh muhadtsah 2) HR management focused on teaching staff through TOT programs and trial classes 3) organizational structure planning coordination and collaboration between managers, Quality guarantors, administrative staff, financial staff, and teaching staff. In this case, the manager has full control over the responsibility of each decision